Contested framings of greenhouse gas removal and its feasibility: Social and political dimensions. (20th May 2020) - Waller, Laurie; Rayner, Tim; Chilvers, Jason; Gough, Clair Amanda; Lorenzoni, Irene; Jordan, Andrew; Vaughan, Naomi
Abstract: Prospective approaches for large‐scale greenhouse gas removal (GGR) are now central to the post‐2020 international commitment to pursue efforts to limit the global temperature increase to 1.5°C. However, the feasibility of large‐scale GGR has been repeatedly questioned. Most systematic analyses focus only on the physical, technical, and economic challenges of deploying it at scale. However, social and political dimensions will be just as important, if not more so, to how possible futures play out. We conduct one of the first reviews of the international peer‐reviewed literature pertaining to the social and political dimensions of large‐scale GGR, with a specific focus on two predominant approaches: Biomass energy with carbon capture and storage (BECCS) and afforestation/reforestation (AR). Our analysis of 78 studies proposes two important insights. First, it shows how six key social and political dimensions of GGR feasibility–namely economics and incentives; innovation; societal engagement; governance; complexity and uncertainty; and ethics, equity, and justice–are identifiable and are emphasized to varying degrees in the literature. Second, there are three contested ways in which BECCS and AR and their feasibility are being framed in the literature: (a) a techno‐economic framing; (b) a social and political acceptability framing; and (c) a responsible development framing. We suggest this third frame will, and indeed should, become increasingly pertinent to the assessment, innovation, and governance of climate futures. This article is categorized under: The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior. Abstract : Co‐word map showing co‐occurance of keywords in the articles reviewed in this paper.